Learning PSD to HTML - Place, David (InfiniteSkills, 2013)
"In this PSD to HTML Using Photoshop and Dreamweaver training course, expert author David Place teaches you the core principles of creating workable websites using these two Adobe programs. This course is designed for users that already have a working knowledge of Photoshop and Dreamweaver. You will start out by creating a PSD mockup using Photoshop. David will teach you about the design basics in Photoshop, layer properties, slicing, and web optimization. From there, you will dive into working in Dreamweaver to transform your Photoshop document into a working website. In Dreamweaver you will explore the process of setting up and managing a website, working with different view modes, and working with images and layout objects. This video tutorial will also teach you some fundamental HTML and CSS rules. Finally, you will work with the Live View in Dreamweaver to test your website. By the completion of this video based training course, you will have developed the necessary skills needed to design, create, and publish a working website. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.